2012
DOI: 10.1021/np2006499
|View full text |Cite
|
Sign up to set email alerts
|

Naphthoquinones from Onosma paniculata Induce Cell-Cycle Arrest and Apoptosis in Melanoma Cells

Abstract: Activity-guided fractionation of a petroleum ether-soluble extract of the roots of Onosma paniculata, which has been shown to affect the cell cycle and to induce apoptosis in melanoma cells, led to the isolation of several shikonin derivatives, namely, β-hydroxyisovalerylshikonin (1), acetylshikonin (2), dimethylacrylshikonin (3), and a mixture of α-methylbutyrylshikonin and isovalerylshikonin (4+5). All compounds exhibited strong cytotoxicity against eight cancer cell lines and MRC-5 lung fibroblasts, with 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 19 publications
5
71
0
1
Order By: Relevance
“…Consistent with the present data, recent studies have observed the suppressive effects of acetylshikonin on the cell growth of several types of cancers, such as gastric carcinoma, melanoma, and colon cancer (Kretschmer et al, 2012;Rajasekar et al, 2012;Zeng et al, 2009). Although a study of the neuronal cell lines reported that acetylshikonin protected those cells from apoptosis (Wang et al, 2013), this neuroprotective role was limited to apoptotic cell death by oxidative stress.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with the present data, recent studies have observed the suppressive effects of acetylshikonin on the cell growth of several types of cancers, such as gastric carcinoma, melanoma, and colon cancer (Kretschmer et al, 2012;Rajasekar et al, 2012;Zeng et al, 2009). Although a study of the neuronal cell lines reported that acetylshikonin protected those cells from apoptosis (Wang et al, 2013), this neuroprotective role was limited to apoptotic cell death by oxidative stress.…”
Section: Discussionsupporting
confidence: 90%
“…1)). Structural identification of all isolated naphthoquinones was performed by spectroscopic techniques listed in experimental part, as well as by comparison of obtained data with those previously published in the literature (Kretschmer et al, 2012[14]; Ozgen et al, 2004[20]; Albreht et al, 2009[1]; Wang et al, 2015[26]; Zhou et al, 2010[27]). Among isolated compounds, 5,8- O -dimethyl isobutyrylshikonin ( 6 ) was found in nature for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…Among 1500 tested quinones, about 150 compounds showed strong in vivo activity against W256 in rats and P388 lymphoid leukemia in mice, as well as significant in vitro potency toward KB cells and CCRF-CEM leukemia cells (Papageorgiou et al, 1999[23]). On the other hand, isolated quinones demonstrated significant in vitro potency toward KB cells, CCRF-CEM leukemia cells, as well as some melanoma cell lines (Papageorgiou et al, 1999[23]; Kretschmer et al, 2012[14]). To determine whether cytotoxicity induced by naphthoquinones was due to apoptosis or cell cycle arrest, the cells were stained with fluorescent dyes and analyzed on flow cytometer.…”
Section: Resultsmentioning
confidence: 99%
“…Shikonin and alkannin derivatives were isolated and identified from plants as described. 19,20 The chemical structures are shown in Figure 1a. Stock solutions were prepared in DMSO and stored at 220 C and were diluted to the final concentration in fresh media before each experiment.…”
Section: Chemicalsmentioning
confidence: 99%